Crop production & field experiememtation - Vaidya V.G. & Sahasrabuddhe K.R., khuspe V.S. (Anmol prakashan, Pune, 1998)
Dry-land Agriculture
ENGLISH
Keywords: Crop production & field experiememtation; Dry-land Agriculture; Dry-land Agriculture